Developing E-Learning Evaluation Instruments: A Study in Vocational School - Nurrahman, Arief; Cahyani, Meita Dwi; Nurfatmawati, Lisa; Wibowo, Hendri (Universitas Negeri Surabaya, 2023)
This study aims to develop instrument for evaluating e-learning through Learning Management System (LMS) in the Office Administration program at vocational schools with CSE-UCLA evaluation model. Using cluster random sampling, data were collected from 85 respondents in the small-scale and 235 in the wide-scale trial stage. Validation procedures included Aiken's index for content validity, while construct validation utilized Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), with reliability assessed using Cronbach's Alpha coefficient. The results showed that there were five instrument constructs for implementing e-learning. The Aiken index to measure content validity showed a valid item. The validity of the instrument construct was evaluated using EFA with a KMO value of 0.751, and each item had an anti-image coefficient more than 0.5, meaning that the factor analysis requirements for the future were met. The fit model based on the CFA result showed the value of Chi-square (X^2) = 239.61, df = 179, P-value = 0.416, RMSEA = 0.000. The loading factor value was 0.41-0.89 (>0.30), meaning the item was valid. The instrument's reliability showed a value of 0.791 that all instruments developed were reliable.